The management of epistaxis in accident and emergency departments: a survey of current practice. - Kotecha, B (1990)
A short questionnaire on the subject of the management of epistaxis was sent to forty accident & emergency departments in two NHS regions. Thirty replies were received (response of 75%). It was found that all departments were involved in the initial management of epistaxis, but the extent of that involvement varied considerably. One of the most obvious factors contributing towards the degree of involvement was the liaison between the accident & emergency and the ENT departments. Three departments never referred patients to the ENT department for follow-up. Nine departments performed their own nasal cautery, but half of these did not use any form of local anaesthesia. Twenty-seven departments used various forms of nasal packing but, of these, two-thirds did not use any form of local anaesthesia. Twenty-three departments allowed patients to go home with a nasal pack in situ. The results of this survey are discussed and a guideline to the management of epistaxis in an accident & emergency setting is suggested.